Developing Social and Emotional Skills of Students with Learning Difficulties Using a Digital Learning Program - Khasawneh, Mohamad Ahmad Saleem (Journal of Ecohumanism, 2024)
This study investigated the impact of using a digital learning program on the development of social and emotional skills among students with learning disabilities in Irbid City, Jordan. Using an experimental design, this research examined how changing one or more independent factors affected the dependent variable. The sampling method we used was a stochastic one. To take part in the research, we randomly chose two classrooms. One classroom served as the experimental group and the other as the control group; with 20 pupils each. There was a significant difference in the average scores for life skills, which include social skills, independent skills, and emotional capacities, between the control and experimental groups. The results suggest that the students in the experimental group possess a substantial amount of practical life skills. The findings provide credence to the idea that students with learning disabilities may benefit from digital learning technologies by increasing their social, emotional, and self-reliance capabilities and hence their adaptive capacities.